Suicide Risk and Hopelessness in Hospitalized Psychiatric Patients - Montaño, Shirley Hawkins; Valencia Zableh, Alberto; Caamaño León, Beatriz; Ceballos Ospino, Guillermo (Pensando Psicología, 2014)
Although hopelessness (H) is known to increase the risk of suicide (RS), this information had not been shown in a representative sample of psychiatric patients hospitalized in Santa Marta (Colombia). This study sought to describe the prevalence of rs and h, and find a link between them according to socio-demographic and clinical variables, in patients with psychiatric disorders. A cross-sectional, correlational descriptive study was conducted, evaluating 61 patients using the Plutchik Suicide Risk Scale, the Beck Hopelessness Scale, and a socio-demographic data survey. The results highlighted that 60.7% of the sample presented rs and 70.4% presented h. A significant correlation was found between rs and h, and also between rs and previous suicide attempts. No correlation was found between RS, H and socio-demographic and clinical variables. In conclusion, the higher the level of H, the higher RS in the study population.
Keywords: hopelessness; psychiatric patients; risk of suicide; prevalence